Implementasi Guru PJOK dalam Penanaman Karakter Peduli Lingkungan pada Siswa SDN 2 Cakranegara - Bagus Dwi Wibowo; Soemardiawan Soemardiawan; Ismail Marzuki (Universitas Hamzanwadi, 2026)
This study was motivated by the poor passing and stopping skills of Karka FC players in 2026, which were caused by a conventional training program that was monotonous and lacked variety. The purpose of this study was to analyze the effect of drop pass drills and team passing competitions on the players’ passing and stopping skills. The research method employed a quantitative approach using a pretest-posttest control group design. The population consisted of 45 players; a sample of 30 players was selected using purposive sampling and divided into an experimental group (15 players) and a control group (15 players). The passing and stopping skills test instrument had been validated for validity (0.89) and reliability (0.87). The training program was conducted over 8 weeks at a frequency of 3 times per week. Data analysis used paired t-tests and independent t-tests at a significance level of α = 0.05. The results showed an average improvement of 59.25% in the experimental group (from 4.27 to 6.80), while the control group improved by 17.38% (from 4.20 to 4.93). The results of the independent t-test showed a calculated t-value of 6.78 > the critical t-value of 2.048 with a p-value of 0.000 < 0.05, indicating a significant difference in improvement between the two groups. The effect size, measured by Cohen’s d, was 2.21, classified as a large effect. The conclusion of this study is that drop pass drills and team passing competitions have a significant effect on improving players’ stopping passing ability.